Influence of Histidine Administration on Ammonia and Amino Acid Metabolism: A Review - Holeček, M (Physiological research, 2020)
Histidine (HIS) is an essential amino acid investigated for therapy of various diseases, used for tissue protection in transplantation and cardiac surgery, and as a supplement to increase muscle performance. The data presented in the review show that HIS administration may increase ammonia and affect the level of several amino acids. The most common are increased levels of alanine, glutamine, and glutamate and decreased levels of glycine and branched-chain amino acids (BCAA, valine, leucine, and isoleucine). The suggested pathogenic mechanisms include increased flux of HIS through HIS degradation pathway (increases in ammonia and glutamate), increased ammonia detoxification to glutamine and exchange of the BCAA with glutamine via L-transporter system in muscles (increase in glutamine and decrease in BCAA), and tetrahydrofolate depletion (decrease in glycine). Increased alanine concentration is explained by enhanced synthesis in extrahepatic tissues and impaired transamination in the liver. Increased ammonia and glutamine and decreased BCAA levels in HIS-treated subjects indicate that HIS supplementation is inappropriate in patients with liver injury. The studies investigating the possibilities to elevate carnosine (beta-alanyl-L-histidine) content in muscles show positive effects of beta-alanine and inconsistent effects of HIS supplementation. Several studies demonstrate HIS depletion due to enhanced availability of methionine, glutamine, or beta-alanine.
Keywords: Liver; Muscle, Skeletal; potravní doplňky; Animals; Dietary Supplements; Histidine; lidé; histidin; kosterní svaly; aminokyseliny; Amino Acids; Humans; zvířata; amoniak; játra; Ammonia